Deglaciation in the central Pyrenees during the Pleistocene–Holocene transition: Timing and geomorphological significance. (15th April 2017) - ,; Aumaître, Georges; Bourlès, Didier L.; Keddadouche, Karim; Palacios, David; García-Ruiz, José M.; Andrés, Nuria; Schimmelpfennig, Irene; Campos, Néstor; Léanni, Laëtitia
Abstract: In this study, we document deglaciation in a sector of the southern–central Pyrenees (the Panticosa massif and the upper Gállego and Ossau valleys) using cosmic-ray exposure (CRE) dating methods, which were applied to samples from high altitude polished rock steps and rock glacier boulders. The obtained CRE dates show a coherent spatial distribution and confirm results previously obtained in this study area, thus demonstrating the reliability and robustness of the method. The results of analyses based on two distinct isotopes ( 10 Be and 36 Cl) are consistent, although the error is higher for results based on the 36 Cl isotope. The study provides evidence for ice extent in the High Gállego Valley during the Oldest Dryas, with glacial advance until the bottom of the valleys, although the main glacier tongues remained disconnected from each other. During this period, the extent of glacier advance was directly related to the elevation of the associated summits. The Younger Dryas glaciers were constrained to cirques or very short ice tongues, and dating of the polished rock steps indicates that the ice masses were present until the first millennium of the Holocene. The Brazato rock glacier developed at the beginning of the Holocene and remained active until the Holocene Thermal Optimum, because of the protective effect of large masses of blocks and boulders. Highlights: Deglaciation of central Pyrenees applying cosmic-ray exposure dating methods with two distinct isotopes (10Be and 36Cl). The results of analyses are consistent, although the 36Cl isotope error is higher. The study provides evidence for the occurrence of a cold stadial during the Oldest Dryas, with important glacier advance. The Younger Dryas glaciers were constrained to cirques or very short ice tongues. A rock glacier developed at the beginning of the Holocene and remained active until the Holocene Thermal Optimums.